APPLYING POSSE STRATEGY IN TEACHINGREADING DESCRIPTIVE TEXT TO THE SENIOR HIGH SCHOOLS STUDENTS - Novia Lorena; Darmawan Budiyanto; Gaya Tridinanti (Universitas Tridinanti Palembang, 2022)
The purpose of this study was to determine whether or not using POSSE Strategy was to find out whether there was a significant difference in students’ reading comprehension between the students who were taught using POSSE strategy and those who were not. There were 80 tenth-grade students taken as the sample selected using purposive sampling, with one group serving as the experimental class and the other serving as the control class. The writers gave pre-test and post-test for experimental and control classes to collect data. This study employed a quantitative approach with a quasi-experimental design. The experimental group was taught using POSSE strategy, while the control group was taught using the discussion strategy. The experimental group's mean score increased from 68.10 in the pre-test to 75.87 in the post-test. Furthermore, the results of independent t-tests from the experimental and control groups revealed that the t-value obtained was 3.060, which was higher than the t-table value of 1.664. It means that the POSSE strategy was effective in improving reading comprehension achievement of the tenth-grade students at SMA Negeri 11 PalembangKeywords:reading comprehension, descriptive text, POSSE strategy